Climate warming promotes deterministic assembly of arbuscular mycorrhizal fungal communities. (8th November 2021) - Xu, Xinyu; Qiu, Yunpeng; Zhang, Kangcheng; Yang, Fei; Chen, Mengfei; Luo, Xi; Yan, Xuebin; Wang, Peng; Zhang, Yi; Chen, Huaihai; Guo, Hui; Jiang, Lin; et al.
Abstract: Arbuscular mycorrhizal fungi (AMF) significantly contribute to plant resource acquisition and play important roles in mediating plant interactions and soil carbon (C) dynamics. However, it remains unclear how AMF communities respond to climate change. We assessed impacts of warming and precipitation alterations (30% increase or decrease) on soil AMF communities, and examined major ecological processes shaping the AMF community assemblage in a Tibetan alpine meadow. Our results showed that warming significantly increased root biomass, and available nitrogen (N) and phosphorus (P) in soil. While precipitation alterations increased AMF abundances, they did not significantly affect the composition or diversity of AMF communities. In contrast, warming altered the composition of AMF communities and reduced their Shannon–Wiener index and Pielou's evenness. In particular, warming shifted the AMF community composition in favor of Diversisporaceae over Glomeraceae, likely through its impact on soil N and P availability. In addition, AMF communities were phylogenetically random in the unwarmed control but clustered in warming plots, implying more deterministic community assembly under climate warming. Warming enhancement of root growth, N and P availability likely reduced plant C‐allocation to AMF, imposing stronger environmental filtering on AMF communities. We further proposed a conceptual framework that integrates biological and geochemical processes into a mechanistic understanding of warming and precipitation changes' effects on AMF. Taken together, these results suggest that soil AMF communities may be more sensitive to warming than expected, highlighting the need to monitor their community structure and associated functional consequences on plant communities and soil C dynamics under the future warmer climate. Abstract : A conceptual framework of warming and precipitation changes on root colonization, extraradical hyphae, community composition, and assembly of arbuscular mycorrhizal fungi (AMF). Warming aggravates N‐limitation of AMF via enhancement of nitrification rate and P availability, and reduces the dependency of plants on AMF through promoting root growth to acquire nutrients, both of which impose stronger environmental filtering on AMF communities. AMF community assembly is estimated by net relatedness index, encompassing environmental filtering if the index is higher than zero, stochasticity if equal to zero, and competitive exclusion if less than zero. Black and red arrows refer to positive and negative effects, respectively.